International survey of injury surveillance practices in competitive swimming - Barry, L.; Lyons, M.; McCreesh, K.; Powell, C.; Comyns, T. (Physical Therapy in Sport, 2022)
Objective The purpose of this study was to identify the injury surveillance practices being used in competitive swimming environments. It explored the nature of the data collected, the injury definitions used and the perceived effectiveness of injury surveillance. Finally, this study also examined barriers to injury surveillance.